PERKEMBANGAN PERUBAHAN BUDAYA TARI TOR TOR CAWAN PADA MASYARAKAT BATAK TOBA - Melody Misbow Siallagan, Ruth; Maulidia Putri, Sabrina; Purba, Mauly (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
Tor-Tor Cawan is one of the ritual ceremonies believed in by the Toba Batak people. The function of this dance is considered as a medium for requests (pinta-pinta) to the Gods and ancestral Spirits, as well as news (narboaboa) and the spiritual world regarding healing of disease, prosperity, rejection of evil (epidemics, evil deeds and natural disasters), even the hope of obtaining offspring. The son who is highly desired by the Batak ethnic group as the successor to the clan. This research was conducted to determine the development and changes in the Tor Tor Cawan dance culture in the Toba Batak Community. This research method is qualitative research. The subjects chosen for this research were the dancers of Sanggar TB Silalahi and the owner of Sanggar TB Silalahi. The data collection techniques used were observation and interviews. The conclusion is that originally the tor tor Cup was a sacred dance used in rites of worship and supplication to God, the Gods and Ancestors. In the current phase, changes have occurred in its function as dance performance and entertainment, as well as changes in the pattern of its production and musical accompaniment. The development of using a cup from 1 to 7 was due to the element of performing arts which became the focus where the acrobatics performed by the dancers made the cups used become 7. The tor tor cup dance is no longer used by the Toba people, but as a prophase dance it is widely performed and disseminated.